Synthesis of sulfonylurea derivatives and their α-glucosidase inhibitory activity - Thi Thoi Bui; Dai Quang Ngo; Van Loc Tran (Vietnam Journal of Science, Technology and Engineering, 2020)
The paper describes the preparation of new sulfonylurea derivatives from sulfonyl carbamate 6 with amino derivatives. The process for synthesis of the key compound 6 included three steps starting from compound 6-chloronicotinic acid 1, which are readily available chemicals. The compound 1 in the presence of triethylamine in anhydrous acetone solvent and ethyl chloroformate to obtain 6-chloronicotinic (ethyl carbonic) anhydride compound 3. The compound 3 were subsequently reacted with compound 4 to obtain compounds 5. The sulfonamides 5 was refluxed with ethyl chloroformate in present anhydrous potassium carbonate in dry acetone to obtain the key compounds 6. The total yield of the key intermediate compound 6 is about 81.35%, related to the starting materials. Finally, three sulfonylurea derivatives 7a-c were synthesized by condensation of 6 with various of amines in toluene. Their structures have been determined by IR, MS and 1H and 13C NMR spectroscopic methods, and their α-glucosidase inhibitory activity have been evaluated.